Physician perceptions and experience of current treatment in actinic keratosis. (27th July 2014) - Stockfleth, E.; Peris, K.; Guillen, C.; Cerio, R.; Basset‐Seguin, N.; Foley, P.; Sanches, J.; Culshaw, A.; Erntoft, S.; Lebwohl, M.
Abstract: Background: Topical therapy is important in the treatment of actinic keratosis (AK), a major risk factor for, and early development stage of, squamous cell carcinoma. Despite this, research addressing the limitations and challenges associated with topical field therapy in actinic keratosis is lacking. Objectives: The aim of this study was to highlight the challenges associated with maximizing compliance in patients receiving topical AK therapy and to investigate real‐world experience with currently available topical therapies including perceptions of adherence and persistence. Methods: A 45‐min online survey was developed and completed by physicians in eight countries. All had previously prescribed topical AK therapy and ≥1 other treatment. Physicians' consensus was summarized as overall agreement/disagreement from ≥70% of respondents (≥60% for case‐specific questions). Results: More than 70% of the 427 respondents agreed that topical field therapy is essential and had concerns that lengthy treatments and local skin reactions caused non‐adherence/persistence. More than 90% of physicians would preferentially prescribe the shortest duration treatment to such patients. Conclusions: The research clarifies the challenges associated with prescribing topical AK therapy and highlights that short treatment duration and rapid clearance of skin reactions are key considerations for physicians. This provides a basis for the generation of recommendations for improving the real‐world efficacy of topical therapy.